(untitled) (Bangladesh Agronomy Journal, 2017)
The residual effect of eight herbicides (pendimethalin, pyrazosulfuron-ethyl, butachlor, pretilachlor, orthosulfamuron, acetochlor + bensulfuron methyl, butachlor + propanil and 2,4-D amine) was applied in unpuddled transplanted aman rice in aa weedy and a hand weeded controls, was evaluated for succeeding crops viz. wheat, lentil and sunflower by following bioassay technique. A study was conducted at Bangladesh Agricultural University, Mymensingh from November 2013 to January 2014 after harvest of unpuddled transplanted aman rice. All herbicides were imposed as weed management practice of unpuddled transplanted aman rice during July to August 2013. The experiment was laid out in a randomized complete block design (RCBD) with three replications. As a consequence, the residual effect of those herbicides on the succeeding wheat, lentil and sunflower crops was evaluated in term of germination, leaf chlorophyll content, seedling shoot length and dry matter. The results showed that seedling germination of all these succeeding crops in the herbicide treated plots did not differ significantly from those of weedy and hand weeded control plots. Moreover, leaf chlorophyll content, seedling shoot length and dry matter of wheat, lentil and sunflower were not adversely affected by any of the herbicide treatments imposed in aman rice. It was concluded that herbicides used in unpuddled transplanted aman rice had no residual effect on the germination and leaf chlorophyll content, seedling shoot length and dry matter of the succeeding wheat, lentil and sunflower crops. Bangladesh Agron. J. 2016 19(2): 95-103